Protective effect of L-glutamine on lysosomal integrity in isopoterenol-induced myocardial infarction in rats - Anandan, Rangasamy; Kumar, Subramaniam Hari Senthil; Sumi, Edakkukaran Sudhakaran; Mathew, Suseela; Ganesan, Balaraman (Acta Biologica Szegediensis, 2015)
Lysosomal acid hydrolases play an imperative part in the initiation of inflammation processes associated with myocardial infarction. In the present investigation, we have studied the protective effect of L-glutamine on isoproterenol-induced myocardial damage in male albino rats with respect to alterations in lysosomal function. The myocardial infarction in experimental animals was induced by intraperitoneal (i.p.) injection of isoproterenol (11 mg/100 g body weight/day) for 2 days. The total and free activities of lysosomal acid hydrolases (β-glucuronidase, β-galactosidase, β-glucosidase and acid phosphatase) were determined in plasma and heart tissue of control and treated rats. Significant elevation in the total activities of lysosomal hydrolases was observed in plasma and heart tissue of isoproterenol administered rats. A parallel (p<0.05) rise in the free activities of these acid hydrolases in the cardiac tissue was also noticed. Isoproterenol-mediated lysosomal membrane fragility was evident from the altered subcellular distribution of heart β-glucuronidase activity. Prior oral administration of L-glutamine (100 mg/kg body weight/day for a period of 20 days) significantly attenuated the isoproterenol-induced release of these lysosomal hydrolases into the systemic circulation from the cardiac lysosomes and maintained the lysosomal stability at level comparable to that of control rats. The results of the present study suggested that the cardioprotective activity of glutamine might be related to its membrane-stabilizing property.